Community-Based Financial Management Models in Supporting Regenerative Tourism in Samosir Regency - Saragih, Vina Gabriella; Yudhistira, Prima; Daryana, Aditiya Pratama (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
This study aims to examine the relationship between community-based financial management models and the success of regenerative tourism in Samosir Regency, Indonesia. Using a mixed approach with sequential explanatory design, data was collected from 150 respondents and 15 key informants in six tourist villages through surveys, interviews, and document analysis. Quantitative findings show that budget participation, financial transparency, and local financial literacy have a significant effect on the effectiveness of regenerative tourism. The thematic analysis also highlights the role of customary institutions and social beliefs in strengthening village financial governance. This research resulted in a contextual logic model that integrates community-based financing with environmental, cultural, and institutional regeneration. These findings contribute to the development of participatory governance theory and provide practical implications in building an inclusive tourism finance system.